A case study on the users' experience of the interior design of selected yoga studios in Metro Manila - Chua, Erika Denise G. (College of Home Economics, University of the Philippines Diliman, 2019)
This research, which utilized a case study approach sought to determine how yoga teachers and yoga students experience comfort in the practice room of four selected yoga studios in Metro Manila. Specifically, this study looked into specific features of elements found in the interior spaces of practice rooms and explained how these provided comfort to the users. Using purposive sampling and snowball sampling, all the 15 yoga teachers interviewed, and 43 yoga students surveyed from the selected yoga studios participated in the study. A case study of qualitative nature was utilized to determine the users' experiences in terms of perceptions and preferences on the interior design elements of yoga practice rooms which were analyzed using the User-centered Theory by Vischer (2008) then categorized under Vischer's physical comfort, functional comfort, and psychological comfort. Results of the study indicate that the selected yoga studios aimed to experience physical comfort by providing safety on the users; experience functional comfort by providing support on the users through flexible interior elements; and experience psychological comfort by providing a welcoming and homey atmosphere to feel comfortable and safe amidst being in a public space. It was found that the experience of the yoga students is greatly affected on how their yoga teachers adjust the interior design elements: sounds, lighting, temperature, and aroma. Therefore, it is important for the yoga teacher to have flexibility on the interior elements to adapt to different situations appropriate for class. Other areas especially communal spaces in the yoga studio may be studied in the future which may influence the feeling of comfort and privacy of users.